The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s00170-015-7807-6
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive control optimization in micro-milling of hardened steels—evaluation of optimization approaches

Abstract: Nowadays, the miniaturization of many consumer products is extending the use of micro-milling operations with high quality requirements. However, the impacts of cutting-tool wear on part dimensions, form and surface integrity are not negligible and part quality assurance for a minimum production cost is a challenging task. In fact, industrial practices usually set conservative cutting parameters and early cutting replacement policies in order to minimize the impact of cutting-tool wear on part quality. Althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Since ACO systems need to be executed in real time, PSO can be a good choice to be implemented in optimization unit of an ACO system. 8 In PSO, each particle has a cognitive factor and a social factor. Cognitive factor determines the trajectories of particles, whereas social factor forces the particle to find its best position and affects the speed of particle.…”
Section: Proposed Aco Proceduresmentioning
confidence: 99%
See 3 more Smart Citations
“…Since ACO systems need to be executed in real time, PSO can be a good choice to be implemented in optimization unit of an ACO system. 8 In PSO, each particle has a cognitive factor and a social factor. Cognitive factor determines the trajectories of particles, whereas social factor forces the particle to find its best position and affects the speed of particle.…”
Section: Proposed Aco Proceduresmentioning
confidence: 99%
“…ACO systems adjust cutting parameters to maximize a given performance index, which can be a function of production cost and material removal rate (MRR), under certain necessary constraints. 8 In the literature, several research works in the field of using ACO systems in machining operations have been reported. Ko and Cho 9 suggested a method for adaptive optimization of cutting parameters for maximizing MRR in milling operation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A review of the AC system is presented in [12]. Three types of ANC's namely identified [13], first one is Adaptive control with constraint (ACC), the second one is Geometry adaptive control (GAC) and the third one is Adaptive control with optimization (ACO). The adaptive controller industrialized in the present study fit into the third classification in which the cutting parameters are calculated and controlled in imperative to optimize a definite index of cutting performance, such as decrease of vibration, amassed of efficiency, enhancement of surface finish, and control of the tool flank wear.…”
Section: Introductionmentioning
confidence: 99%